2023
DOI: 10.1186/s12931-023-02347-z
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of transient receptor potential (TRP) channels by plant derived substances used in over-the-counter cough and cold remedies

Abstract: Background Upper respiratory tract infections (URTIs) impact all age groups and have a significant economic and social burden on society, worldwide. Most URTIs are mild and self-limiting, but due to the wide range of possible causative agents, including Rhinovirus (hRV), Adenovirus, Respiratory Syncytial Virus (RSV), Coronavirus and Influenza, there is no single and effective treatment. Over-the-counter (OTC) remedies, including traditional medicines and those containing plant derived substance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 155 publications
0
15
0
1
Order By: Relevance
“…Additionally, published data indicated that the activation of TRPM8 channels might result in the production of inflammatory mediators [ 48 ]. There is still some controversy over the current data, as some studies have suggested that the activation of TRPM8 channels inhibits the cough response [ 49 , 50 ]. However, the results of this study indicated that TRPM8, as a differentially expressed gene, was downregulated after exposure to cigarette smoke but activated after exercise training, which suggested a positive role for TRPM8 in improving pulmonary function in mice with COPD through exercise.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, published data indicated that the activation of TRPM8 channels might result in the production of inflammatory mediators [ 48 ]. There is still some controversy over the current data, as some studies have suggested that the activation of TRPM8 channels inhibits the cough response [ 49 , 50 ]. However, the results of this study indicated that TRPM8, as a differentially expressed gene, was downregulated after exposure to cigarette smoke but activated after exercise training, which suggested a positive role for TRPM8 in improving pulmonary function in mice with COPD through exercise.…”
Section: Discussionmentioning
confidence: 99%
“…Some of these plant extracts are likely to include a mixture of compounds with varying degrees of medicinal properties. 29 For example, eucalyptus oil consists of multiple different chemical compounds at different concentrations, which may have varying interactions with the TRP channels studied. Furthermore, the three and four VVRI mixtures utilized do not represent the exact concentration of each ingredient used in Vicks VapoRub.…”
Section: Discussionmentioning
confidence: 99%
“…The URT infections are often accompanied by symptoms such as cough, sore throat, and breathing difficulties, which are difficult to treat with single antipathogen therapy. 14,15 L-menthol serves as a cooling mimic and activator of the cold-sensitive transient receptor potential melastatin-8 (TRPM8) channels. 16,17 It stimulates the TRPM8 channels of the trigeminal nerve in the airways, inducing a cooling sensation, and thereby alleviating symptoms of throat pain, inflammation, and dyspnea.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, it is evident that the bactericidal and antiviral capabilities of I 2 are highly valuable for application against URT infections. The URT infections are often accompanied by symptoms such as cough, sore throat, and breathing difficulties, which are difficult to treat with single antipathogen therapy. , l -menthol serves as a cooling mimic and activator of the cold-sensitive transient receptor potential melastatin-8 (TRPM8) channels. , It stimulates the TRPM8 channels of the trigeminal nerve in the airways, inducing a cooling sensation, and thereby alleviating symptoms of throat pain, inflammation, and dyspnea. Therefore, the anti-inflammatory properties of l -menthol combined with the bactericidal and antiviral effects of I 2 can be utilized to the maximum extent in alleviating and treating URT infection symptoms through codelivery after being loaded into suitable carriers.…”
Section: Introductionmentioning
confidence: 99%